PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN PT. PEMBANGUNAN PERUMAHAN (PERSERO) TBK. PROYEK PEGADAIAN TOWER JAKARTA - Indah Dwi Saputri; Imam Wibowo (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
Purpose this study aims to determine the effect of leadership and organizational culture on employee productivity at PT. Pembangunan Perumahan (Persero) Tbk. Pegadaian Tower Jakarta Project. This research was conducted to employees of PT. Pembangunan Perumahan (Persero) Tbk. Pegadaian Tower Jakarta Project. Data were obtained using a questionnaire with a differential semantic scale. The sampling technique used is a saturated sample. Tthe results of research, leadership, Organizational Culture partially has a significant effect on employee productivity. Leadership and organizational culture simultaneously have a significant effect on Employee Productivity.